The Influence of Green Marketing on Purchase Intention with Green Brand Image as a Mediating Variable - Firanti Sabilla; Roslina Roslina (Universitas Muhammadiyah Tangerang, 2026)
Public awareness of environmental issues continues to increase, encouraging companies to implement sustainability-oriented marketing strategies. However, there is still a gap between the implementation of green marketing and the level of consumer understanding and interest in purchasing environmentally friendly products. This study aims to examine the influence of green marketing on purchase intention, with green brand image as a mediating variable, among The Body Shop consumers in Bandar Lampung. This study used a quantitative method with a causal design. A total of 180 respondents were selected through purposive sampling, then the data were analyzed using Partial Least Squares (PLS) with the help of SmartPLS software. The research findings show that green marketing has a positive and significant influence on both green brand image and purchase intention. Green brand image is also proven to have a positive influence on purchase intention and is able to mediate the relationship between green marketing and purchase intention. Overall, these results confirm that The Body Shop's environmentally conscious marketing efforts are able to build a strong green brand image, thereby increasing consumer trust and purchase intention.Keyword:Â Green Marketing, Green Brand Image, Purchase Intention, The Body Shop